RASIONALISASI RETRIBUSI PELAYANAN PASAR DI KOTA PEKANBARU - Tio Karolina Damanik; Zaili Rusli SD (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The Receipt of market of market retribution has been increased every year, but vied from the target set market retribution, it has not reached the target in each year. This showed that the implementation of collecting market retribution in Pekanbaru City was not optimal yet. One of the effort made by the Regional Goverment in managig market retribution was to provide service to trader. The problem studied was the acceptance of arket retribution which constantly icreased whether it had been balanced with good quality market service from the Departement of Trade ad Industry of Pekanbaru city to maret trader. The aim of this research was to describe the rationalization of market service restribution in Pekanbaru city by examing he quality of market service. The research used descriptive qualitative data analysis technique with qualitative research method using descriptive approach and the data needed were both primary and secondary data that was obtained through observation, interview, and documentation then analyzed based on research quesion. The results of this research indicate that changes in regional regulation and management of facilities and market cleanliness had not bee rettional according to the service quality t improve service and market charge. The physical facilities of the market were not well maintained yet, the lacking management of empty stalls and booths, there were some stalls and booths were still dameged. Judging from the reliability readiness lack od Departement of Trade and Industry of Pekanbaru in helping trade. Departement of Trade and Industry of Pekanbaru’s response in responding trade’ complaints were also lacking, seen from the guarantee Departement of Trade and Industry of Pekanbaru were not skilled enough in serving trader and empathy indicator, were not optimal yet since it was only accommodate the aspiration oftrader. Factors that hampered market service in Pekanbaru City were the lack of human Resource management, hampered fund and public awareness.Keyword: Rationalization, Retribution, Service